2015
DOI: 10.1039/c5ra18476b
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of a natrolite zeolite/palladium nanocomposite and its application as a reusable catalyst for the reduction of organic dyes in a very short time

Abstract: A natrolite zeolite/palladium (natrolite zeolite/Pd) nanocomposite has been successfully synthesized applying a simple in situ reduction method using an aqueous extract of fruits of Piper longum as a reducing and stabilizing agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Silver has long been recognized as having an inhibitory effect on microbes present in a medical and industrial process [36,37]. In medicine, silver and AgNPs used as ointments to [18][19][20][21][22][23] prevent infection against burn and open wounds [1,38]. Additionally, the broad biocidal effect of the biologically synthesized of AgNPs through breaks the cell membrane and disturbs the protein synthesis mechanism in the bacterial system.…”
Section: Application Of Silver Nanoparticles (Agnps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Silver has long been recognized as having an inhibitory effect on microbes present in a medical and industrial process [36,37]. In medicine, silver and AgNPs used as ointments to [18][19][20][21][22][23] prevent infection against burn and open wounds [1,38]. Additionally, the broad biocidal effect of the biologically synthesized of AgNPs through breaks the cell membrane and disturbs the protein synthesis mechanism in the bacterial system.…”
Section: Application Of Silver Nanoparticles (Agnps)mentioning
confidence: 99%
“…Nowadays, metal based nanoparticles are synthesized for numerous applications from different plant parts such as leaves, roots, flower, seeds etc. For instance, Cu/Fe 3 O 4 nanoparticles from Silybum marianum L. Seed extract [12], Cu/reduced graphene oxide/Fe 3 O 4 nanocomposite from Euphorbia wallichii leaf extract [13], Gold nanoparticles (AuNPs) from Anthemis xylopoda flower aqueous extract [14], Palladium nanoparticles from the Hippophae rhamnoides linen leaf extract [15], Pd/Fe 3 O 4 nanoparticles from Euphorbia condylocarpa M. bieb root extract [16], Palladium nanoparticles (PdNPs) from Sour Cherry tree Gum [10], Copper nanoparticles supported on bentonite (bentonite/CuNPs) from Thymus vulgaris L. leaf extract [17], Pd nanoparticles supported on graphene oxide from barberry fruit extract [18], Natrolite zeolite/Pd nanocomposite using Piper longum fruits extract [19], Cu/reduced graphene oxide (RGO-Fe 3 O 4 ) using nanocomposite Berberis vulgaris fruit extract [20], CuO nanoparticles by aqueous extract of Anthemis nobilis flowers [21], AuNPs by Anthemis xylopoda flowers [22], CuNPs using Ginkgo biloba L. leaf extract [23], PdNPs using Euphorbia thymifolia L. leaf extract [24], CuNPs using Euphorbia esula L leaves extract [25], PdNPs using Hippophae rhamnoides linn leaf extract [15], Pd/Fe 3 O 4 nanoparticles using Euphorbia condylocarpa M. bieb root extract [26], Au/Pd bimetallic nanoparticles from Euphorbia condylocarpa M. bieb [27], biosynthesis of AgNPs for application Ag/bone nanocomposite Myrica gale L. extract [28], Ag/RGO/Fe 3 O 4 using Lotus garcinii leaf extract for nano-catalyst [29], AgNPs using Gongronema latifolium leaf extract [30], green synthesis of PdNPs using Salvia hydrangea extract for catalyitic reduction of dyes [31], green synthesis of AgNPs supported on waste peach kernel shell using Achillea millefolium L. extract [32], synthesis of Ag/ Fe3O4 nanocomposite using Euphorbia peplus Linn leaf extract [33], and synthesis of Pd/perlite nanocomposite using Euphorbia neriifolia L. leaf extract [34].…”
Section: Introductionmentioning
confidence: 99%
“…3 a. Amornkitbamrung et al [101] demonstrated the reduction of palladium ions with acidic/alkaline-treated sucrose as a reducing agent. The reduction mechanism is schematically shown in Piper longum fruit extract PdCl 2 and Natrolite zeo-lite~1 2.5 nm [195] Theobroma cacao L. seeds extract (Pd/CuO) PdCl 2 and CuCl 2 Á2H 2 O 40 nm [191,192] It was also suggested that the Pd ions should be introduced into the reaction mixture within 15 min of the alkaline degradation to achieve better reducing efficiency by the produced aldehyde species. Dauthal and Mukhopadhyay [44] expressed their view in the reduction of PdCl 2 to PdNPs presumably by polyol compounds.…”
Section: Pd-ion Reduction By Plant Extractsmentioning
confidence: 99%
“…19 Barberry fruit extract was used to prepare Pd NPs/RGO by green synthesis to catalyze the reduction of nitroarenes. 20 Many green materials including coffee and tea extract, 21 beet juice, 22 piper longum fruits extract, 23 Euphorbia thymifolia L. leaf extract, 24 Theobroma cacao L. seeds extract, 25 Euphorbia neriifolia L. leaf extract, 26 Gardenia taitensis leaf extract, 27 Solanum melongena plant extract, 28 Cucurbita pepo leaf extract 29,30 have been used to prepare Pd NPs. Ginkgo biloba leaf extract was used as a reducing and stabilizing agent to prepare copper nanoparticles, 31 silver nanoparticles 32 and gold nanoparticles.…”
Section: Introductionmentioning
confidence: 99%